Design of Columns Centrically Loaded in Compression - Nikolic, Ruzica R.; Veljkovic, Jelena M.; Vican, Jozef (Communications - Scientific letters of the University of Zilina, 2007)
Design of centrically loaded columns by the axial compressive load is considered in this work. The three methods results are compared: theoretical -procedure and calculations according to standards JUS U.E7.081and Eurocode 3. The analysis is illustrated on an example of a column with a complex cross-section. By comparison between the calculated normal stresses and should be allowable stresses for all the three procedures, one can see that the stresses calculated using both standard procedures are significantly smaller than stresses calculated using the theoretical procedure. This shows that the standard procedures of calculations and design are much more on the safety side, especially in the case of Eurocode 3.